Pengaruh periode perendaman air dan komposisi media tumbuh terhadap keberhasilan aklimatisasi planlet sagu (Effect of water immersion period and growing media composition on acclimatization success of sago palm plantlets ) - . SUMARYONO; Imron RIYADI (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2017)
Sago palm (Metroxylon sagu Rottb.) is a carbohydrate-producing crop, commonly propagated by suckers. The availability of planting materials in a large quantity hinders the development of commercial sago plantations. Sago propagation by tissue culture via somatic embryogenesis has been developed to provide superior planting materials of sago palm. One of the major problems faced in tissue culture of sago palm is the low survival rate of plantlets during acclimatization period. The objective of this research was to increase the acclimatization success of sago plantlets in term of survival rate and growth at ex vitro conditions. The experiments were conducted using a randomized block design with two factors i.e. water immersion period and growing media composition. The water immersion periods used were without immersion, immersion for 2 days with 1 day intermittent period, immersion for 1 day with 1 day intermittent period, immersion for 1 day with 2 days intermittent period, and continuous immersion. The growing media used were consisted of top soil, sand, dung manure, and cocopeat at different compositions. Sago plantlets were planted on small plastic pots and placed inside a closed plastic tunnel for 12 weeks. Research results showed that continuous water immersion and mixed composition of soil, sand, and cocopeat (1:1:2 v/v) was the best conditions for acclimatization of sago plantlets with the survival rate of 70% after 12 weeks. The survived plants had good leaves and roots, ready to be transferred to big plastic bags in the main nursery. [Keywords: Metroxylon sagu, sago palm, acclimatization, immersion, media composition] AbstrakTanaman palma sagu (Metroxylon sagu Rottb.) termasuk tanaman penghasil karbohidrat yang umumnya diperbanyak dengan anakan (suckers). Ketersediaan bahan tanam dalam jumlah besar merupakan hambatan pengembangan perkebunan sagu komersial. Kultur jaringan tanaman sagu telah dikembangkan melalui teknik embriogenesis somatik untuk memenuhi kebutuhan bahan tanam unggul sagu. Salah satu masalah utama dalam kultur jaringan sagu adalah rendahnya daya hidup planlet pada tahap aklimatisasi. Penelitian ini bertujuan meningkatkan keberhasilan aklimatisasi planlet sagu yang meliputi daya hidup dan pertumbuhan bibit pada lingkungan ex vitro. Percobaan dilakukan menggunakan rancangan acak kelompok dengan dua faktor yaitu perendaman air dan komposisi media. Perlakuan perendaman air adalah tanpa perendaman, perendaman 2 hari diselang tanpa perendaman 1 hari, perendaman 1 hari diselang tanpa perendaman 1 hari, perendaman 1 hari diselang tanpa perendaman 2 hari, dan perendaman terus menerus. Komposisi media tumbuh yang digunakan berupa perbandingan volume penyusun yaitu tanah, pasir, pupuk kandang dan cocopeat. Planlet ditanam di pot kecil dan diletakkan di dalam sungkup plastik tertutup selama 12 minggu. Hasil penelitian menunjukkan bahwa perlakuan perendaman terus menerus dan media tumbuh campuran tanah, pasir, cocopeat (1:1:2 v/v) merupakan kondisi terbaik pada aklimatisasi planlet sagu dengan daya hidup mencapai 70% setelah 12 minggu. Bibit yang dihasilkan memiliki daun dan perakaran yang baik, siap untuk dipindahkan ke pot plastik besar di persemaian utama.[Kata kunci: Metroxylon sagu, sagu, aklimatisasi, perendaman, komposisi media]